Prevalensi Reaksi Transfusi Darah Penderita Talasemia Beta Mayor yang Bergantung Transfusi di RSD Idaman Banjarbaru Tahun 2020-2021 - Tasya Radhia Salsabila; Harapan Parlindungan Ringoringo; Roselina Panghiyangani; Edi Hartoyo; Rahmiati Rahmiati (Homeostasis, 2022)
Abstract: Patients with beta thalassemia major require regular and routine blood transfusions throughout life to maintain hemoglobin levels in order to survive. Blood transfusion in patients with beta thalassemia major who depend on transfusion can cause side effects and unwanted transfusion reactions. Transfusion reactions range from mild to life-threatening. The purpose of this study was to obtain data on the prevalence of transfusion reactions in transfusion-dependent beta thalassemia patients at Idaman Hospital Banjarbaru in 2020-2021. This study is a descriptive study that was taken retrospectively using patient medical record data. The results showed that there were 131 data on blood transfusion reactions of patients with beta thalassemia major who were dependent on transfusion from a total of 1591 data on transfusion at Idaman Hospital Banjarbaru for the period October 2020 - September 2021 with a prevalence of 8.2%. Moderate-severe transfusion reactions were the most common type, with 90 blood transfusion reactions (68.7%). The five main symptoms of a blood transfusion reaction that occur are fever, chills, pruritus, angioedema, and urticaria. All transfusion reactions that occurred were acute transfusion reactions and used PRC blood components. Keywords: beta thalassemia major, transfusion dependent, blood transfusion, transfusion reactions, PRC (Packed Red Cells) Abstrak: Pasien talasemia beta mayor memerlukan transfusi darah secara teratur dan rutin sepanjang hidup untuk mempertahankan kadar hemoglobin guna bertahan hidup. Transfusi darah pada penderita talasemia beta mayor yang bergantung transfusi dapat menimbulkan efek samping dan reaksi transfusi yang tidak diinginkan. Reaksi transfusi tersebut dari ringan sampai mengancam jiwa. Tujuan penelitian ini adalah memperoleh data prevalensi reaksi transfusi penderita talasemia beta mayor yang bergantung transfusi di RSD Idaman Banjarbaru Tahun 2020-2021. Penelitian ini merupakan penelitian deskriptif yang diambil secara retrospektif menggunakan data rekam medis pasien. Hasil penelitian menunjukkan bahwa terdapat 131 data reaksi transfusi darah penderita talasemia beta mayor yang bergantung transfusi dari total 1591 data transfusi di RSD Idaman Banjarbaru periode Oktober 2020 – September 2021 dengan prevalensi sebesar 8,2%. Reaksi transfusi sedang-berat merupakan jenis yang paling banyak terjadi sebanyak 90 reaksi transfusi darah (68,7%). Lima gejala utama dari reaksi transfusi darah yang terjadi adalah demam, menggigil, pruritus, angioedema, dan urtikaria. Semua reaksi tranfusi yang terjadi adalah reaksi transfusi akut dan menggunakan jenis komponen darah PRC. Kata-kata kunci: talasemia beta mayor, bergantung transfusi, transfusi darah, reaksi transfusi, PRC (Packed Red Cells)